Relationship between marriage readiness and pregnancy planning among prospective brides - Novita Rahmah; Wiwit Kurniawati (SAGE Publishing, 2021)
Background: The growing marriage rates need to be followed with marriage readiness and pregnancy planning to become parents. The readiness of marriage includes age readiness, physical, financial, mental, emotional, social, moral, interpersonal, intellectual, and life skills. Unprepared marriage can have an impact on domestic violence and divorce. The readiness of marriage should be balanced with the existence of important pregnancy planning carried out to realize reproductive rights responsibly and the government program movement 1000 The First Day of Life as a golden period of child development, and avoid unplanned pregnancy in 4T conditions. Marriage readiness of prospective bride affects the readiness to maintain health of children in the future. Design and Methods: This research aimed to determine the relationship between marriage readiness and pregnancy planning among prospective brides. A correlative descriptive design with a cross-sectional method is used with a convenience sampling technique in determining the respondents, and obtained a total of 258 respondents. Results: The results showed a meaningful relationship between marital readiness and pregnancy planning (p=0.000, α=0.05). Conclusions: This study recommends education of pregnancy planning and readiness before marriage, both physical and psychological, with interactive media and nurse cooperation with community cadres in socialization on wedding preparation and preconceptions that are not only attended by prospective brides, but also women of childbearing age and adolescence in minimizing misinformation in unmarried women.